Structural features of diverse Pin-II proteinase inhibitor genes from capsicum annuum - Mahajan, Neha S.; Dewangan, Veena; Lomate, Purushottam R.; Joshi, Rakesh S.; Mishra, Manasi; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2015)
The proteinase inhibitor (PI) genes from Capsicum annuum were characterized with respect to their UTR, introns and promoter elements. The occurrence of PIs with circularly permuted domain organization was evident. Several potato inhibitor II (Pin-II) type proteinase inhibitor (PI) genes have been analyzed from Capsicum annuum (L.) with respect to their differential expression during plant defense response. However, complete gene characterization of any of these C. annuum PIs (CanPIs) has not been carried out so far. Complete gene architectures of a previously identified CanPI-7 (Beads-on-string, Type A) and a member of newly isolated Bracelet type B, CanPI-69 are reported in this study. The 5' UTR (untranslated region), 3'UTR, and intronic sequences of both the CanPI genes were obtained. The genomic sequence of CanPI-7 exhibited, exon 1 (49 base pair, bp) and exon 2 (740 bp) interrupted by a 294-bp long type I intron. We noted the occurrence of three multi-domain PIs (CanPI-69, 70, 71) with circularly permuted domain organization. CanPI-69 was found to possess exon 1 (49 bp), exon 2 (551 bp) and a 584-bp long type I intron. The upstream sequence analysis of CanPI-7 and CanPI-69 predicted various transcription factor-binding sites including TATA and CAAT boxes, hormone-responsive elements (ABRELATERD1, DOFCOREZM, ERELEE4), and a defense-responsive element (WRKY71OS). Binding of transcription factors such as zinc finger motif MADS-box and MYB to the promoter regions was confirmed using electrophoretic mobility shift assay followed by mass spectrometric identification. The 3' UTR analysis for 25 CanPI genes revealed unique/distinct 3' UTR sequence for each gene. Structures of three domain CanPIs of type A and B were predicted and further analyzed for their attributes. This investigation of CanPI gene architecture will enable the better understanding of the genetic elements present in CanPIs.
Keywords: CanPI; Capsicum; Gene architecture; Promoter; Proteinase inhibitor

Fusarium oxysporum mediates systems metabolic reprogramming of chickpea roots as revealed by a combination of proteomics and metabolomics - Kumar, Yashwant; Zhang, Limin; Panigrahi, Priyabrata; Dholakia, Bhushan B.; Dewangan, Veena; Chavan, Sachin G.; Kunjir, Shrikant M.; Wu, Xiangyu; Li, Ning; Rajmohanan, Pattuparambil R.; Kadoo, Narendra Y.; Giri, Ashok P.; et al. (Plant Biotechnology Journal, 2016)
Molecular changes elicited by plants in response to fungal attack and how this affects plant-pathogen interaction, including susceptibility or resistance, remain elusive. We studied the dynamics in root metabolism during compatible and incompatible interactions between chickpea and Fusarium oxysporum f. sp. ciceri (Foc), using quantitative label-free proteomics and NMR-based metabolomics. Results demonstrated differential expression of proteins and metabolites upon Foc inoculations in the resistant plants compared with the susceptible ones. Additionally, expression analysis of candidate genes supported the proteomic and metabolic variations in the chickpea roots upon Foc inoculation. In particular, we found that the resistant plants revealed significant increase in the carbon and nitrogen metabolism; generation of reactive oxygen species (ROS), lignification and phytoalexins. The levels of some of the pathogenesis-related proteins were significantly higher upon Foc inoculation in the resistant plant. Interestingly, results also exhibited the crucial role of altered Yang cycle, which contributed in different methylation reactions and unfolded protein response in the chickpea roots against Foc. Overall, the observed modulations in the metabolic flux as outcome of several orchestrated molecular events are determinant of plant's role in chickpea-Foc interactions.
Keywords: Chickpea; fusarium oxysporum; Metabolomics; NMR; plant-pathogen interaction; proteomics

GAME9 regulates the biosynthesis of steroidal alkaloids and upstream isoprenoids in the plant mevalonate pathway - Cardenas, Pablo D.; Sonawane, Prashant D.; Pollier, Jacob; Vanden Bossche, Robin; Dewangan, Veena; Weithorn, Efrat; Tal, Lior; Meir, Sagit; Rogachev, Ilana; Malitsky, Sergey; Giri, Ashok P.; Goossens, Alain; et al. (Nature Communications, 2016)
Steroidal glycoalkaloids (SGAs) are cholesterol-derived molecules produced by solanaceous species. They contribute to pathogen defence but are toxic to humans and considered as anti-nutritional compounds. Here we show that GLYCOALKALOID METABOLISM 9 (GAME9), an APETALA2/Ethylene Response Factor, related to regulators of alkaloid production in tobacco and Catharanthus roseus, controls SGA biosynthesis. GAME9 knockdown and overexpression in tomato and potato alters expression of SGAs and upstream mevalonate pathway genes including the cholesterol biosynthesis gene STEROL SIDE CHAIN REDUCTASE 2 (SSR2). Levels of SGAs, C24-alkylsterols and the upstream mevalonate and cholesterol pathways intermediates are modified in these plants. Delta(7)-STEROL-C5(6)-DESATURASE (C5-SD) in the hitherto unresolved cholesterol pathway is a direct target of GAME9. Transactivation and promoter-binding assays show that GAME9 exerts its activity either directly or cooperatively with the SlMYC2 transcription factor as in the case of the C5-SD gene promoter. Our findings provide insight into the regulation of SGA biosynthesis and means for manipulating these metabolites in crops.

Integrated transcriptomic and proteomic analyses suggest the participation of endogenous protease inhibitors in the regulation of protease gene expression in helicoverpa armigera - Lomate, Purushottam R.; Dewangan, Veena; Mahajan, Neha S.; Kumar, Yashwant; Kulkarni, Abhijeet; Wang, Li; Saxena, Smita; Gupta, Vidya S.; Giri, Ashok P. (Molecular & Cellular Proteomics, 2018)
Insects adapt to plant protease inhibitors (PIs) present in their diet by differentially regulating multiple digestive proteases. However, mechanisms regulating protease gene expression in insects are largely enigmatic. Ingestion of multi-domain recombinant Capsicum annuum protease inhibitor-7 (CanPI-7) arrests growth and development of Helicoverpa armigera (Lepidoptera: Noctuidae). Using de novo RNA sequencing and proteomic analysis, we examined the response of H. armigera larvae fed on recombinant CanPI-7 at different time intervals. Here, we present evidence supporting a dynamic transition in H. armigera protease expression on CanPI-7 feeding with general down-regulation of protease genes at early time points (0.5 to 6 h) and significant up-regulation of specific trypsin, chymotrypsin and aminopeptidase genes at later time points (12 to 48 h). Further, coexpression of H. armigera endogenous PIs with several digestive protease genes were apparent. In addition to the differential expression of endogenous H. armigera PIs, we also observed a distinct novel isoform of endogenous PI in CanPI-7 fed H. armigera larvae. Based on present and earlier studies, we propose potential mechanism of protease regulation in H. armigera and subsequent adaptation strategy to cope with anti-nutritional components of plants.

Plant protease inhibitors induced oxidative and nutritional stress in helicoverpa armigera unveils multifaceted survival strategies: a lipidomic and metabolomic view - Dewangan, Veena; Gupta, Sonu Kumar; Deshpande, Neha; Lomate, Purushottam R.; Kumar, Yashwant; Giri, Ashok P. (ACS Omega, 2026)
Plant protease inhibitors impede insect growth and development by targeting digestive proteases. In response, insects adapt by modulating protease expression; however, their survival may not rely solely on digestive plasticity and likely involves broader physiological adjustments. To investigate this, we performed an integrated lipidomic and metabolomic analysis of Helicoverpa armigera larvae fed on the recombinant Capsicum annuum protease inhibitor (rCanPI-7), a four-domain inhibitor with potent activity against insect trypsins and chymotrypsins. The results revealed extensive metabolic reprogramming in H. armigera under rCanPI-7-induced stress, prominently affecting amino acid, glutathione, and pyrimidine metabolic pathways with distinct shifts in alanine, arginine, histidine, and branched-chain amino acid metabolism. Suppression of glycolysis and the tricarboxylic acid cycle indicated reduced primary energy metabolism, while oxidative stress was evident from glutathione depletion, lipid peroxidation, and ceramide accumulation, which are hallmarks of mitochondrial dysfunction. To offset this metabolic imbalance, H. armigera mobilized triglycerides and amino acids as alternative energy sources. Reinforcing antioxidant defenses, membrane remodeling, and activating apoptotic and neuromodulatory pathways plausibly aided in restoring cellular homeostasis. Collectively, these findings reveal a tightly coordinated physiological tug of war in H. armigera, where the detrimental effects of rCanPI-7-induced oxidative and nutritional stress were countered through compensatory metabolic, structural, and signaling adjustments. This study provides the first lipidomic insight into this pest species, offering a deeper understanding of its biochemical resilience and potential metabolic vulnerabilities for targeted biopesticide strategies.